NEW CULTIVARS OF CUCUMBER FOR OPEN FIELD CONDITIONS. BUSH TYPE CUCUMBER - I.B. Korotseva (Ovoŝi Rossii, 2011)
The article includes the detailed description of newly developed «Korotyshka» cultivar of cucumber of bush type. Agro-technical features for short-climbing cultivars were also given.